Pelatihan dan Pendampingan Penulisan Karya Ilmiah Berbasis STEAM bagi Guru dan Siswa MTS Negeri 2 Surakarta - Nurhasanah, Farida; Usodo, Budi; Chrisnawati, Henny Ekana; Kuswardi, Yemi; Sutopo, Sutopo; Rahayu, Eni Puji (FKIP Universitas Sebelas Maret, 2023)
One of the efforts to realize the vision and mission of the Government Islamic Junior High School 2 Surakarta (MTS N 2 Surakarta) to be one of the best schools at the national level is by participating in MYRES (Madrasah Young Researcher Super Camp), which conducted annually by the Indonesian Ministry of Religion. The school have participated in this event several times, but unfortunately, the result still needs improvement. After conducting a self-evaluation, there found some possible aspects that caused this situation. The lack of knowledge and experience in conducting research and writing academic articles of the teachers who became students’ supervisors indicated the main problem that caused this situation. Based on this situation, the Government Islamic Junior High School 2 Surakarta (MTS N 2 Surakarta), in collaboration with the Contemporary Mathematics Education Research Group of the Mathematics Education Department, Sebelas Maret University, has conducted intensive training for academic writing to be submitted to MYRES competition. This program was conducted for three months, from April to June 2022. This program comprised of some activities, a workshop on academic writing with a keynote from Yogyakarta State University, continued by intensive training conducted online and offline. Ten proposals resulted from this program, ten were submitted to MYRES, and two of the proposal finally can compete until the semifinal stage.